Pengaruh Literasi Keuangan, Pengetahuan Investasi, dan Motivasi Terhadap Minat Berinvestasi Saham Syariah Mahasiswa Program Studi Manajemen Bisnis Syariah Universitas Muhammadiyah Sumatera Utara - Andi Perkasa Tarigan; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of financial literacy, investment knowledge, and motivation on interest in investing in sharia shares among students of the Sharia Business Management Study Program, Muhammadiyah University of North Sumatra. The method used is quantitative, using data obtained from questionnaires filled out by 71 respondents. The research results show that investment knowledge and motivation significantly influence interest in investing in sharia shares, with regression coefficient values ​​of 0.480 and 0.521 respectively. In cont. Financial literacy did not show a significant impact. These findings indicate that focusing on increasing investment knowledge and motivation can increase students' interest in investing in Islamic shares.